2014
DOI: 10.1111/acv.12139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human presence on the long‐term trends of migrant and resident shorebirds: evidence of local population declines

Abstract: This study examines the responses to human presence of the most abundant shorebird species in an important coastal migration staging area (Los Lances Beach, southern Spain). Long‐term census data were used to assess the relationship between bird abundances and human densities and to determine population trends. In addition, changes in individual bird behaviour in relation to human presence were evaluated by direct observation of a shorebird resident species. Our results show that a rapid increase in the recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 32 publications
0
41
1
Order By: Relevance
“…In these large mudflats, waterbirds can position themselves far away from humans, which makes disturbance to be low. Other studies have also shown that the disturbing effect of human presence mainly occurred in narrow beaches (Lafferty, 2013;Martín et al, 2014). Second, most waterbirds, notably small species, seemed to be habituated to the presence of clam harvesters and did not perceive them as predators, especially as these clam harvesters generally moved slowly and were completely indifferent against birds.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In these large mudflats, waterbirds can position themselves far away from humans, which makes disturbance to be low. Other studies have also shown that the disturbing effect of human presence mainly occurred in narrow beaches (Lafferty, 2013;Martín et al, 2014). Second, most waterbirds, notably small species, seemed to be habituated to the presence of clam harvesters and did not perceive them as predators, especially as these clam harvesters generally moved slowly and were completely indifferent against birds.…”
Section: Discussionmentioning
confidence: 95%
“…Second, most waterbirds, notably small species, seemed to be habituated to the presence of clam harvesters and did not perceive them as predators, especially as these clam harvesters generally moved slowly and were completely indifferent against birds. Previous studies have shown that the disturbance of waterbirds was mainly due to people engaged in recreational activities and/or accompanied by domestics animals (Navedo and Herrera, 2012;Lafferty et al, 2013;Martín et al, 2014). Finally, it is possible that shorebirds benefited from clam harvesting activity, as turning over the sediment makes the invertebrates more available for shorebirds, especially for visual foragers.…”
Section: Discussionmentioning
confidence: 99%
“…; Martín et al . ). Additionally, our study measured only the immediate redistribution of birds as a result of recreational use at small spatial scales (600‐m length of foreshore) and did not capture any chronic effects of disturbance over a larger spatial and temporal scale.…”
Section: Discussionmentioning
confidence: 97%
“…In some cases, temporary or permanent avoidance of suitable habitat can occur (Meager, Schlacher & Nielsen ; Lafferty, Rodriguez & Chapman ; Martín et al . ), ultimately reflected in lower local abundance, physiological condition or reproductive success (Gill ; Steven, Pickering & Castley ; Weston et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic causes are the form most commonly studied (Weston et al , p. 269) and are the focus of this discussion. Arising in a variety of forms, disturbance has been identified as limiting populations and species (Glover et al , p. 326; Koch and Paton , p. 58; Whitfield and Rae , p. 57; Martín et al , p. 73). Less evident than the direct species take, disturbance is a more cryptic and insidious form of damage.…”
Section: Introductionmentioning
confidence: 99%